2017
DOI: 10.1007/s12272-017-0955-5
|View full text |Cite
|
Sign up to set email alerts
|

Pro-oxidant status and Nrf2 levels in psoriasis vulgaris skin tissues and dimethyl fumarate-treated HaCaT cells

Abstract: Reactive oxygen species (ROS) contribute to pathogenesis of many inflammatory skin diseases, including psoriasis. The aim of this study is to compare antioxidant protein expression in psoriasis vulgaris (PV) skin tissues with that in normal skin tissues in vivo and to evaluate the effects of dimethyl fumarate (DMF), used for the treatment of psoriasis, on ROS generation and apoptosis in a human keratinocyte cell line HaCaT. Compared with normal skin tissues, PV skin tissues showed increased protein oxidation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…DMF, dimethyl fumarate; I/R, ischemia-reperfusion; MPO, myeloperoxidase types of cells, including keratinocytes, fibroblasts, endothelial cells, neuron cells. 25,31,34,35 We newly found the antioxidative effect of DMF on H 2 O 2 -derived ROS in mouse pericytes-like cells in vitro.…”
Section: Dmf Suppressed Ros Production Caused By Oxidative Stress Imentioning
confidence: 89%
“…DMF, dimethyl fumarate; I/R, ischemia-reperfusion; MPO, myeloperoxidase types of cells, including keratinocytes, fibroblasts, endothelial cells, neuron cells. 25,31,34,35 We newly found the antioxidative effect of DMF on H 2 O 2 -derived ROS in mouse pericytes-like cells in vitro.…”
Section: Dmf Suppressed Ros Production Caused By Oxidative Stress Imentioning
confidence: 89%
“…Additional confirmation of the role of oxidative stress in the course of Ps are the results of clinical trials in which antioxidant supplementation resulted in a significant improvement in general status of psoriatic patients [59]. So far, systemic changes at the transcription level have not been studied, and only the local reduction of Nrf2 transcriptional activity in the skin of psoriasis patients has been found [24]. Therefore, Nrf2 transcriptional activity reduced in inflammatory cells of our patients with PsA suggest this could be important pathophysiological parameter specific for this type of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is suggested that oxidative stress may activate mechanisms that restore the redox balance, including activation of Nrf2 transcription factor, which is responsible for antioxidant and cytoprotective gene transcription [22,23]. However, a reduction in Nrf2 activity was observed in the skin of psoriatic patients [24].…”
Section: Introductionmentioning
confidence: 99%
“…Persistent overactivation of AHR by TCDD and other dioxin-related compounds induces prolonged oxidative stress and may cause chloracne (51,68,69). The generation of ROS is also involved in the pathogenesis of contact dermatitis, AD and psoriasis (70)(71)(72). Therefore, antioxidative AHR agonists may be beneficial for the treatment of oxidative inflammatory skin diseases.…”
Section: Regulatory Role Of Aryl Hydrocarbon Receptor In Oxidative Stmentioning
confidence: 99%